Consumer Responses to the COVID-19 Crisis: Evidence from Bank Account Transaction Data - Asger Lau Andersen; Emil Toft Hansen; Niels Johannesen; Adam Sheridan (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
This paper uses transaction-level customer data from the largest bank in Denmark to estimate the change in consumer spending caused by the COVID-19 pandemic and the resulting shutdown of the Danish economy. We find that aggregate spending was on average 27% below the counterfactual level without the pandemic in the seven weeks following the shutdown. The spending drop was mostly concentrated on goods and services whose supply was directly restricted by the shutdown, suggesting a limited role for spillovers to non-restricted sectors through demand in the short term. The spending drop was larger for individuals with more ex ante exposure to the adverse consequences of the crisis in the form of job loss, wealth destruction, severe disease and disrupted consumption patterns and, most notably, for individuals with an ex post realization of crisis-related unemployment.
Keywords: D12; H31; I18; 330; COVID-19; consumer spending; pandemic; social distancing; shutdown